Assessment of quality of health of native ethnic tribes of cold desert Leh- Ladakh - G.M. Rather (National Geographical Journal of India, 2022)
The present study was carried out to assess the Quality of Heath of Native ethnic tribes of cold desert Leh - Ladakh. These ethnic tribes being the inhabitants of remote areas of cold desert are lagging behind in almost all the basic facilities and their overall living condition is not conducive for human health. The study reveals that the number of health institutions were only 1.83 per 1000 population. Overall rate of morbidity was 18.83 percent. Near about 96.84 per cent households were having supply of drinking water by taps but regular water supply was noted only in 20.87 per cent households. Near about 70.39 percent households in urban areas were having dustbins but disposal of waste in dustbins was noted in only 17.96 per cent of households. About 62.62 percent of households were having drainage facility but majority of households (54.37%) were having open drainage. All these worse housing conditions leads to worst health conditions of people. The main objective of the present study was to analyse the housing characteristics of ethnic population in different blocks and come up with the suggestions for the improvement of same that will lead to better health conditions.